Toward a Just Circular Economy: Synergizing Waste Transformation within Indonesia’s Difapreneur and Skizopreneur Programs - Muhammad Adhim; Regina Heart Dwi Cahya (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The implementation of the circular economy (CE) is often constrained by the dominance of profit-oriented logic, ignopring essential social pillars like justice and inclusivity. This study aims to explore the distinctive circular economy model embedded in the Difapreneur and Skizopreneur programs in Denpasar, Bali, which integrate social sustainability into environmental practices. Employing an exploratory case study approach, data were collected through in-depth interviews with persons with disabilities, schizophrenia survivors, and facilitators from PT Pertamina Patra Niaga Fuel Terminal Sanggaran. These data were complemented by analyses of strategic documents and reports on environmental impact. The findings reveal that the transformational synergy of coffee grounds waste into herbal incense has successfully created a new value chain that economically and socially empowers marginalized groups. In addition to providing a real ecological solution by mitigating methane emissions, the program effectively redistributes power by transforming vulnerable groups from passive aid recipients into autonomous economic actors. This study highlighted that the transition toward a just circular society can be achieved by pursuing environmental restoration alongside the reduction of social inequalities and the enhancement of human dignity.